Improved Numerical Integration Algorithm for Electrical Parameter Measurement - Huang, Jian-zhong; Liao, Han-xin; Hang, Qing-le; Chen, Gang (2020 7th International Conference on Information Science and Control Engineering (ICISCE), 2020)
The principle of improved numerical integration algorithm is introduced and the simulation on the algorithm has been carried out. The effects of the first sample point and frequency offset on the measurement accuracy have been analyzed in details. The performances of the improved numerical integration algorithm and conventional numerical integration algorithm have been compared. The simulation results come to the conclusion that the improved numerical integration algorithm has high accuracy in measuring voltage, current and active power. And the relative errors of the measurement results are within 0.02%.